Demographic Change of the Kawauchi Special Nursing Home Occupants in a Former Evacuation Area After the Nuclear Power Plant Accident: A Retrospective Observational Study. (19th September 2023) - Kobashi, Yurie; Nishikawa, Yoshitaka; Morita, Tomohiro; Omata, Fumiya; Ito, Naomi; Tsubokura, Masaharu
Abstract: Objective: This retrospective observational study aimed to look into the social demographic change of the occupants of a long-term care (LTC) facility that was constructed in 2015 as a restoration support after the Fukushima Daiichi nuclear power plant accident. Methods: The social demographic information during 2015–2021 of occupants in the Kawauchi Special Nursing Home was analyzed. Results: A total of 172 participants were included in the analysis. The number (proportion) of evacuees was 37 (69.8%) in 2015, then gradually decreased to 7 (31.8%) in 2018, yet increased to 21 (58.3%) in 2019. There were 121 occupants (70.4%) who were from Kawauchi Village and other municipalities of the former evacuation area. Conclusion: The Kawauchi Special Nursing Home initially received people who hoped to return to the former evacuation zone; however, its role changed to receive people who became in need of LTC after returning to Kawauchi Village. The construction of LTC facilities in the former evacuation area may help enhance the local LTC service where returnees are rapidly aging.